Review on Quantum Communication and Quantum Computation - Chen, Jiajun (Journal of physics. Conference series, 2021)
Quantum communication has made great breakthroughs in recent years. Because of its characteristics for strict information security transmission and high speed, it has received attention from related research fields around the world. This paper briefly reviews the progress in the field of quantum computing and communication. The basic functions of quantum mechanics related to the quantum communication are first introduced, including qubit, logic gates, postulates, polarization and quantum entanglement. Then the applications of quantum communication are discussed including teleportation, cryptography and quantum networks. Finally, advantages and disadvantages for the current applications are analyzed and the challenges remained in the current research are demonstrated.